Restorative Justice in Medical Cases: Reflections on Criminal Law Reform - Nandar, M Aris Munandar; Amir Ilyas; Said Karim; Syamsuddin Muchtar (Jurist-Diction, 2025)
The reform of Indonesian criminal law signals a paradigm shift from a retributive model to a restorative approach grounded in fairness and humanity. This study seeks to explore how restorative justice may serve as a mechanism for resolving medical cases within the broader context of national criminal law reform. To address this question, the research relies on normative legal analysis, drawing on statutory provisions together with scholarship in criminal law, health law, and human rights. The analysis indicates that restorative justice provides a potentially fair and proportional response to medical cases, especially those involving medical personnel acting under situational pressures. Yet, the absence of detailed procedural guidelines and the overlap of authority between professional organizations and law enforcement agencies pose significant obstacles. The study concludes that stronger regulatory and institutional frameworks are required to ensure the effective and consistent application of restorative justice in the criminal justice system.